Critical success factors and contractual risks for private finance 2 (PF2) projects implementing Building Information Modelling (BIM) - Siti Nora Haryati Abdullah Habib (School of the Build Environment, University of Salford, 2017)
Private Finance 2 (PF2) projects involved multiple stakeholders engaged in various contract structures, and numerous stages from initiation to operation in lengthy contract duration. Such situation cause complexity to PF2 projects, which may expose the projects to risks mainly related to collaborative networking, information integration, and contractual relationships. The emergence of Building Information Modelling (BIM) in the construction industry is an immense achievement that can potentially assist the industry players to mitigate risks in PF2 projects. Notwithstanding such benefits, BIM also exposes its users to contractual risks when the barriers in sharing information are reduced. Therefore, this study investigates the key contractual risks and the strategies to mitigate the risks for PF2 projects implementing BIM. The study also considers the critical success factors (CSFs) for PF2 projects implementing BIM as these are the aspects underlying the mitigating strategies. Subsequently, this study develops a conceptual framework of contractual risks management for PF2 projects implementing BIM. The study is within the pragmatism philosophy; therefore it employs concurrent embedded mixed method strategy that combines qualitative and quantitative approaches. There are two stages of the study. At the first stage, data were collected through literature review, questionnaire survey and unstructured interviews with the industry experts. The results were then used to develop the preliminary conceptual framework of contractual risks management. In the second stage of the study, semi-structured interviews were carried out with the industry experts to validate the conceptual framework. Content analysis, thematic analysis, and mind mapping methods were used for the analysis of the qualitative data; whereas, descriptive and inferential statistical analyses were used for the analysis of the quantitative data. These have lead to the development of a holistic conceptual framework that illustrates the interconnection of the CSFs, contractual risks and the risks management strategies. The study suggests fourteen CSFs for PF2 projects implementing BIM. Five CSFs are considered as the most dominant, which are: (1) systematic workflows, coordination and integration; (2) good understanding on BIM; (3) technical competence; (4) robust and clear contractual provisions; and (5) effective collaboration among the project participants. In relation to this, the study also identifies eighteen BIM risk factors that can give significant impact towards PF2 projects, most of which are related to contractual issues and BIM competency. The study reveals twenty-two contractual risks for PF2 projects implementing BIM which are related to (1) information management; (2) data reliance; (3) status of BIM model; (4) intellectual property rights; and (5) liability issues. Twenty-four strategies to manage the contractual risks were identified by the study. Based on the findings, the study implies that the PF2 projects implementing BIM require seamless and collaborative contractual instrument that is able to link all stages in the project delivery, to make the project contractually organised for a lengthy period of time, and to sustain collaborative environment throughout the project duration.The conceptual framework suggested in this study is considered relevant for implementation to meet the needs of PF2 projects implementing BIM as it would help the Clients and PF2 Contractors in the process of negotiating and drafting their contractual provisions. The study is original as it addresses the use of BIM from the contractual perspective, through the lens of PF2 projects.